2022
DOI: 10.36227/techrxiv.19698001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defect Detection in Bi-directional Glass Fabric Reinforced Thermoplastics Based on 3D THz Imaging

Abstract: Non-homogeneous, bi-directional glass fabric reinforced thermoplastic (GFRT) composites are used in the automobile industry to produce economic, environmentally friendly and recyclable vehicles. Despite the fact that GFRT materials have superior mechanical characteristics and lower manufacturing cost compared with traditional materials, they are prone to significant deformation and defect emergence during the forming/manufacturing of parts from prefabricated laminates. Some defects, especially hidden ones like… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Therefore, various non-destructive testing (NDT) techniques are investigated for the understanding of defect formation and evolution as well as for the application in production monitoring of GFRT components [7]. Examples for NDT techniques applied to composite materials include ultrasonic imaging [8,9], THz imaging [10,11,12], X-ray computed tomography [11] or infrared thermography [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, various non-destructive testing (NDT) techniques are investigated for the understanding of defect formation and evolution as well as for the application in production monitoring of GFRT components [7]. Examples for NDT techniques applied to composite materials include ultrasonic imaging [8,9], THz imaging [10,11,12], X-ray computed tomography [11] or infrared thermography [13].…”
Section: Introductionmentioning
confidence: 99%
“…Defects in composite materials include delamination (i.e., separation of fiber layers), consolidation (i.e., variations of the polymer matrix thickness), local fiber shifts (i.e., local agglomeration of fibers in one layer leaving behind a hole in the fabric of this layer), global fiber shift (i.e., lateral offset of one fabric layer with respect to the others) or cracks (i.e., broken fibers in one or more fabric layer). For GFRT it has been demonstrated that delamination and consolidation can be detected by THz imaging [12]. In this study, we are aiming to provide a proof of concept for the detection of local fiber shifts in GFRT by means of X-ray scattering with EI.…”
Section: Introductionmentioning
confidence: 99%